The Effect of Spectators’ Cultural Values and their Involvement on the Attitude Towards the Contents of the Television Series - Rojas-Lamorena, Álvaro José; Alcántara-Pilar, Juan Miguel; Sánchez-Duarte, Iván Manuel; Rodríguez-López, Mª Eugenia (Journal of Tourism, Sustainability and Well-being, 2019)
The purpose of this research is to verify that attitudes towards the contents included in a television series are affected by the level of involvement of the viewer with it and by the cultural dimensions at the individual level. Through a self-administered questionnaire, a sample of 240 subjects whose data is submitted to ANCOVA is obtained. The data show significant differences in attitudes toward violence, sex and stereotypes included in television series, such as Game of Thrones, depending on the level of involvement of the viewer. In addition, they also demonstrate the effect of individual cultural values on the attitudes of viewers on television content. This research yields information of interest for the audiovisual sector given that at high levels of involvement, viewers will present more favourable attitudes towards the contents of the television series. On the other hand, cultural values also play an important role in the perception and attitude of the spectators, affecting significantly. They will also be more prone to interaction, creating content and buying related objects. Consequently, it would be key, for companies in the sector, the analysis and empowerment of the audience’s involvement. This research provides new data regarding the involvement of viewers with television series and the attitudes they present to the different contents included in them, analysing the specific case of a current series such as Game of Thrones. In addition, the sixth dimension of Hofstede, Hofstede and Minkov (2010) is proposed and validated at the individual level, as a contribution to literature.